Axial-piston hydraulic machines - field of application and performance indicators - Viunyk, Olha; Boltukov, K.; В’юник, Ольга Володимирівна (Запоріжжя : 2023, 2023)
EN: Quantitative characteristics of one or more properties, in relation to certain conditions of creation and operation of machines, are called machine quality indicators. One of the most important generalizing properties of machines is reliability. With regard to agricultural, construction and road machines, reliability can be characterized as the ability to maintain within a certain time the values of all parameters that characterize the machine's ability to perform the necessary functions under the specified modes and conditions of use, maintenance, storage and transportation. Being a complex property, reliability, depending on the purpose of mobile machines (construction, road, agricultural) and their operating conditions, may include reliability, durability, maintainability and preservation or certain combinations of these properties. Construction and road machines include motor graders, bulldozers, excavators, scrapers, specialized vehicles, agricultural forage and grain harvesters, etc. In their design, due to its advantages, a hydraulic drive has found wide application. More than 90% of single-bucket excavators produced in the country have a hydraulic drive, and 100% of motor graders. The share of means of mechanization of construction with a hydraulic drive exceeds 50%.
Keywords: pump-hydromotor; GST-90 hydraulic drive; hydraulic units; hydraulic machines